Moving target detection for polarimetric multiple-input multiple-output radar in Gaussian clutter - Li, Na; Cui, Guolong; Kong, Lingjiang; Liu, Qing Huo (IET radar, sonar & navigation, 2015)
This study deals with the problem of moving target detection (MTD) for polarimetric multiple-input multiple-output (MIMO) radar in the presence of Gaussian clutter. The authors extend the framework for MTD with MIMO radar to a generic number polarisation channels case. Within the polarimetric framework, the new generalised likelihood ratio test for moving target is first proposed. Then, the target velocity estimation problem is investigated. The maximum-likelihood (ML) estimator for target velocity is developed, and the corresponding Cramer–Rao bound is derived which serves as a benchmark of the estimation performance. Next, the adaptive version of the new polarimetric detector is considered. The covariance matrix is estimated using the sample covariance matrix and the model-based strategies based on the secondary data. Finally, several numerical simulations of the proposed polarimetric detector and ML estimator with typical parameters are obtained and discussed.